HEALTH RELATED QUALITY OF LIFE AS A NEW INSTRUMENT IN EXTANDED EVALUATION OF PATIENTS WITH GI DISEASES - A.A. Baranov; A.S. Potapov; E.S. Dublina; E.V. Komarova ("Paediatrician" Publishers LLC, 2006)
The article provides literature survey of health related quality of life (HRQL) in patients with gastrointestinal tract (GI tract) disorders focusing on it's application in pediatrics. The review defines the term of healtharelated quality of life and presents the HRQL questionnaires specially developed for patients with different GI tract disorders indicating possible areas of their use. The article summarizes the reports assessing the healtha related quality of life in adults with GI disorders and disclose the literature survey of the state of the matter in pediatrics.Key words: GI disorders, quality of life, children.